2022
DOI: 10.1007/s00125-022-05716-3
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-specific effects of a long-term lifestyle intervention on body weight and cardiometabolic health markers in adults with prediabetes: results from the diabetes prevention study PREVIEW

Abstract: Aims/hypothesis Lifestyle interventions are the first-line treatment option for body weight and cardiometabolic health management. However, whether age groups or women and men respond differently to lifestyle interventions is under debate. We aimed to examine age- and sex-specific effects of a low-energy diet (LED) followed by a long-term lifestyle intervention on body weight, body composition and cardiometabolic health markers in adults with prediabetes (i.e. impaired fasting glucose and/or impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…These results were independent of baseline characteristics (e.g., greater body weight of men). Our results add to existing evidence about the sex-specific effects of a lifestyle intervention on weight loss, cardiometabolic health and insulin resistance ( 9 , 59 63 ).…”
Section: Discussionsupporting
confidence: 78%
“…These results were independent of baseline characteristics (e.g., greater body weight of men). Our results add to existing evidence about the sex-specific effects of a lifestyle intervention on weight loss, cardiometabolic health and insulin resistance ( 9 , 59 63 ).…”
Section: Discussionsupporting
confidence: 78%
“…Current ADA guidelines recommended that adults with prediabetes be screened every year for diabetes and be referred to a lifestyle intervention to encourage weight loss [ 16 ]. Nevertheless, the diabetes prevention study PREVIEW, which included younger, middle-aged and older adults, found that older adults benefited less from a lifestyle intervention in relation to cardiometabolic health markers than younger adults, despite greater weight loss [ 23 ]. The findings of the current study support less aggressive treatment to cardiovascular disease prevention in older adults with prediabetes than in middle-aged ones with prediabetes, given the low risk of subclinical atherosclerosis among older adults with prediabetes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a post-hoc analysis of the diabetes prevention study PREVIEW also suggested that younger adults achieved greater improvement in body composition and cardiometabolic markers from lifestyle intervention than older adults. 32 Our results called for age-stratified preventive strategies, in particular early screening for prediabetes and intervention in young people who have the potential to benefit more from the prevention efforts. Secondly, prediabetes itself is associated with major clinical events even excluding people who subsequently developed diabetes and adjusting for metabolic factors.…”
Section: Discussionmentioning
confidence: 95%